STRUKTUR BIAYA PRODUKSI USAHATANI PAPRIKA DENGAN TEKNIK PENGAIRAN IRIGASI TETES - Reina Ayu Cecilia; Sulistyodewi Nur Wiyono; Zumi Saidah; Pandi Pardian (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Paprika is one of the horticultural commodities that has the opportunity to be cultivated because of high demand. However, the amount of paprika production has not been able to fulfill the existing demand, so one of the efforts is to increase the productivity by applying the drip irrigation system. The application of these techniques leads to high costs while various aspects of paprika farming are always changing and can change the level of profits. Analysis of the structure of production costs is needed to determine the amount of costs incurred in paprika farming with the application of drip irrigation system. The purpose of this research is to explain the structure of production costs of paprika farming by applying the drip irrigation system. The analytical method used is descriptive quantitative method. The results shows the production costs incurred per year is Rp364.514.570,00 with an average fixed cost of Rp184.837.320,00 per year and the average variable cost of Rp179.677.250,00 per year. The value of investment shows a Net B / C of 2,66, which means it is profitable.